A comparative retrospective analysis: myocutaneous flap versus skin flap in V-Y medial epicanthal fold reconstruction - Wang, Bulin; Zhang, Shengchang; Chen, Yi; Liu, Zhihong; Yu, Jiangang; Zhou, Huimin; Pan, Er (Frontiers in Surgery, 2024)
Objectives: To evaluate the comparation of myocutaneous flap versus skin flap in V-Y medial epicanthal fold reconstruction.Methods: The study, conducted from April 2017 to June 2022, involved two groups: group A, comprising 21 patients who underwent medial epicanthal fold restoration surgery using the V-Y advancement method with a skin flap, and group B, comprising 83 patients who underwent the same procedure, while with a myocutaneous flap for orbicularis oculi ring reconstruction. Intercanthal distances were measured preoperatively, recorded during preoperative and postoperative reviews, and assessed through a 4-point Likert satisfaction questionnaire.Results: A total of 104 patients were followed up for 6 months postoperatively. In group A, preoperative intercanthal distances ranged from 28.7 mm to 38.2 mm, increasing to 30.2 mm to 40.6 mm postoperatively, with a mean increase of 3.0 mm (P < 0.05). In group B, preoperative distances ranged from 28.8 mm to 38.0 mm, increasing to 32.2 mm to 41.5 mm postoperatively, with a mean increase of 3.9 mm (P < 0.05). Group B exhibited a higher overall satisfaction rate compared to group A.The myocutaneous flap V-Y procedure, employing the principle of orbicularis oculi ring reconstruction, achieves more stable postoperative results than the flap-only V-Y procedure. Consequently, it can be regarded as the preferred surgical technique.